2021
DOI: 10.1371/journal.pone.0253769
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and longitudinal changes in fasting glucose levels: A nationwide cohort study

Abstract: We investigated the association between oral hygiene indicators of periodontitis, tooth loss, and tooth brushing on the longitudinal fasting glucose level in non-diabetic subjects. Using a nationwide health screening database in Korea, we included non-diabetic individuals who received a health screening program with oral health check in 2009–2010. We constructed a linear mixed model for the longitudinal data of fasting glucose from the baseline to 2015. During the 4.84-year of median follow-up, 91,963 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 46 publications
5
23
0
Order By: Relevance
“…In this study, we demonstrated that less frequent toothbrushing was associated with higher risk DM, which is in line with previous ndings 14, [23][24][25] . A recent meta-analysis including 20 studies showed that a lower frequency of toothbrushing was associated an increased risk of DM (OR:1.32, 95% CI:1.19-1.47) 23 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we demonstrated that less frequent toothbrushing was associated with higher risk DM, which is in line with previous ndings 14, [23][24][25] . A recent meta-analysis including 20 studies showed that a lower frequency of toothbrushing was associated an increased risk of DM (OR:1.32, 95% CI:1.19-1.47) 23 .…”
Section: Discussionsupporting
confidence: 93%
“…A national cohort study from Korea (mean age 56) suggested that frequent toothbrushing may decrease fasting glucose levels 25 . Similar in southwest China, a cohort study (mean age 44) reported that compared with almost no tooth brushing, tooth brushing at least twice a day was associated with a 45% reduction (HR=0.65, 95% CI:0.45-0.94) in DM events 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A possible connection between tooth loss and diabetes is via periodontal disease [ 52 ]. Data from a South Korean Nationwide Health Screening Program showed that the FBG correlated with periodontitis and tooth loss but not with dental caries [ 53 ]. In the study of de Miguel-Infante et al [ 36 ], the subjects with diabetes had an increased ratio of periodontal disease by 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that low frequency of tooth brushing may be a risk factor of hypertension and T2DM were in accordance with some previous studies. 11 , 18 , 31 A recent meta‐analysis (one cohort study, 14 case‐control studies, and five cross‐sectional studies) reported that the lowest frequency of tooth brushing was significantly associated with an increased risk of diabetes (OR:1.32; 95% CI: 1.19–1.47) compared with the highest frequency. 27 An intervention study in Japan ( N = 182) showed a significant improvement of tooth brushing frequency and systolic blood pressure in the intervention group (dental health education group) compared with the non‐intervention group.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 Recently, several studies have shown that periodontal treatment is beneficial to control their BP or glucose for patients with periodontitis. 16 , 17 , 18 Microbiological plaque, the main pathogenesis in the development of periodontal disease, should be regularly and effectively cleaned from all surfaces of teeth in order to prevent periodontal disease. 19 , 20 , 21 Oral health has been previously reported to be related with CVD and this association varied by age, sex, socioeconomic status, residence, education levels, smoking, alcohol use and body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%